Mom's guide to child NObesity an illustrated guide book on child obesity and proper, nutritious and balanced meal preparations for mothers in Metro Manila - Vicente, Pamela Beatriz C.; Austria, Romanlito S. (Quezon City College of Fine Arts, University of the Philippines Diliman, 2018)
There is a very one-sided view of what malnutrition is in our country. Most media present nutritional problems as underweight and undernutrition, due to this other effects of improper nutrition have been overlooked and been allowed to grow. Child overweight and obesity is something not often talked about in the Philippines, but throughout the years it has been a consistently expanding problem that can no longer be ignored.

One of the biggest contributors to this problem is improper and unhealthy foods made available to these kids. With that being said, changing and improving the eating habits of these children are vital in keeping away and solving the child overweight and obesity problem of the country. Parents, especially mothers, play a big part when it comes to establishing a more balanced, proper and healthy diet among these children.

With the world becoming more and more dependent on visuals, this is a study that is aimed on developing an illustrated guide book that will put the nutritional focus on overweight and obesity while promoting balanced and nutritional eating habits among children for mothers in Metro Manila. In making use of illustrations, this material aspires to bring light to the said issue and motivate change among mothers by presenting it through a more direct and approachable manner.
Thesis (Bachelor of Fine Arts in Visual Communication)--University of the Philippines Diliman
Bibliography: leaves 111-112
Keywords: Obesity in children; Nutrition; Meal -- Preparation